Emerging Applications of Atomic Layer Deposition for Lithium-Ion Battery Studies - Meng, Xiangbo; Yang, Xiao-Qing; Sun, Xueliang (Advanced materials (Weinheim), 2012)
Lithium‐ion batteries (LIBs) are used widely in today's consumer electronics and offer great potential for hybrid electric vehicles (HEVs), plug‐in HEVs, pure EVs, and also in smart grids as future energy‐storage devices. However, many challenges must be addressed before these future applications of LIBs are realized, such as the energy and power density of LIBs, their cycle and calendar life, safety characteristics, and costs. Recently, a technique called atomic layer deposition (ALD) attracted great interest as a novel tool and approach for resolving these issues. In this article, recent advances in using ALD for LIB studies are thoroughly reviewed, covering two technical routes: 1) ALD for designing and synthesizing new LIB components, i.e., anodes, cathodes, and solid electrolytes, and; 2) ALD used in modifying electrode properties via surface coating. This review will hopefully stimulate more extensive and insightful studies on using ALD for developing high‐performance LIBs. Atomic layer deposition (ALD) is a highly tunable technique for fabricating various nanostructured materials that can potentially be used in lithium‐ion batteries (LIBs) as anodes, cathodes, or inorganic solid electrolytes. It is also a viable approach to coat electrode materials of LIBs for improved performance.